Mengeksplorasi Pengalaman Psikologis Remaja Korban Bullying - Putri Natasya Serliacy Sirait (Wacana Psikokultural, 2023)
This research aims to explore the psychological experiences of adolescent victims of bullying and identify effective psychological intervention strategies in addressing the psychological effects, specifically anxiety disorders, experienced by bullying victims. This study employs an analytical approach and interviews to gain a profound understanding of the psychological experiences of bullying victims, encompassing their feelings, thoughts, emotional reactions, and the link between bullying experiences and the development of anxiety disorders in adolescents. Based on the research findings, several proposed interventions with significant influence from a clinical psychology perspective include: implementing Cognitive-Behavioral Therapy (CBT) as the primary approach in psychological interventions, providing psychosocial support through individual and group counseling, conducting regular psychological monitoring and evaluation, and fostering collaboration with mental health service centers. These findings are expected to offer guidance in designing effective intervention strategies to assist bullying victims in overcoming the psychological impacts they encounter.